Improved mechanical and tribological properties of (TiZrHfNbTa)C with the addition of silicon carbide whiskers - Lenka Ďaková; Alexandra Kovalčíková; Monika Hrubovčáková; Jana Andrejovská; František Kromka; Ján Dusza (Open Ceramics, 2024)
Dense (Ti0.2Zr0.2Hf0.2Nb0.2Ta0.2)C with up to 10 wt % SiC whisker were prepared by spark plasma sintering. The influence of SiCw on the microstructure development, mechanical and tribological properties has been investigated. Nanohardness of HEC and SiCw phases varied between 38 GPa and 40 GPa, and indentation modulus of elasticity was ∼605 GPa. The hardness of the composites increased from 22 GPa to 27 GPa and indentation fracture resistance from 3.55 MPa m1/2 to 4.59 MPa m1/2 with increasing SiCw content. The main toughening mechanisms were crack deflection, crack branching, and crack bridging. The system HEC +5 wt% of SiCw was found to possess the highest bending strength of 623 ± 25 MPa. The composites exhibited similar coefficients of frictions with around 0.3 and wear rates approximately 1.50 × 10−6 mm3/N⋅m at 5 N and 2.66 × 10−6 mm3/N⋅m at 25 N with positive influence of SiC phase on the wear mechanisms.